2021
DOI: 10.1186/s12958-020-00692-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and its possible relationship with endometrial receptivity in adenomyosis: a preliminary study

Abstract: Background Adenomyosis (AM) is an important cause of female infertility. However, the underlying mechanism remains unclear. This report describes a preliminary study of hypoxia and its possible association with endometrial receptivity in AM. Methods The study was divided into in vitro and in vivo experiments. In vitro, expression levels of the endometrial receptivity markers HOXA10 and HOXA11 in the implantation period were examined using real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 28 publications
1
18
0
3
Order By: Relevance
“…It is currently believed that the abnormal expression of cell adhesion molecules in the endometrial epithelial cells of patients with adenomyosis affects blastocyst implantation (24). Our tissue assay con rmed that the expression of HOXA10 and LIF markers associated with endometrial receptivity were abnormally reduced in infertile patients with adenomyosis.…”
Section: Discussionsupporting
confidence: 61%
“…It is currently believed that the abnormal expression of cell adhesion molecules in the endometrial epithelial cells of patients with adenomyosis affects blastocyst implantation (24). Our tissue assay con rmed that the expression of HOXA10 and LIF markers associated with endometrial receptivity were abnormally reduced in infertile patients with adenomyosis.…”
Section: Discussionsupporting
confidence: 61%
“…Studies have shown that the hypoxic microenvironment also affects female reproductive capacity, which can result in failing to provide adequate oxygen to implantation failure after embryo transfer in patients with adenomyosis. However, there are no research reports on the relationship between hypoxic microenvironment and endometrial receptivity in infertile patients with adenomyosis [ 209 , 210 ].…”
Section: Methodsmentioning
confidence: 99%
“…HIF-1α is the most ubiquitously expressed of the three isoforms and has 48% amino acid sequence identity to HIF-2α ( Fitzpatrick, 2019 ). It has been reported that HIF-1α and HIF-2α played a key role in the acute and chronic response to hypoxia, respectively ( Galan-Cobo et al, 2015 ; Guo et al, 2021 ). Due to the existence of multiple HIF-3α variants, it is less well characterized.…”
Section: Overview Of Hifmentioning
confidence: 99%